Endogenous BiP reporter system for simultaneous identification of ER stress and antibody production in Chinese hamster ovary cells - Kyeong, Minji; Lee, Jae Seong (Metabolic Engineering, 2022)
As the biopharmaceutical industry expands, improving the production of therapeutic proteins using Chinese hamster ovary (CHO) cells is important. However, excessive and complicated protein production causes protein misfolding and triggers endoplasmic reticulum (ER) stress. When ER stress occurs, cells mediate the unfolded protein response (UPR) pathway to restore protein homeostasis and folding capacity of the ER. However, when the cells fail to control prolonged ER stress, UPR induces apoptosis. Therefore, monitoring the degree of UPR is required to achieve high productivity and the desired quality. In this study, we developed a fluorescence-based UPR monitoring system for CHO cells. We integrated mGFP into endogenous HSPA5 encoding BiP, a major ER chaperone and the primary ER stress activation sensor, using CRISPR/Cas9-mediated targeted integration. The mGFP expression level changed according to the ER stress induced by chemical treatment and batch culture in the engineered cell line. Using this monitoring system, we demonstrated that host cells and recombinant CHO cell lines with different mean fluorescence intensities (MFI; basal expression levels of BiP) possess a distinct capacity for stress culture conditions induced by recombinant protein production. Antibody-producing recombinant CHO cell lines were generated using site-specific integration based on host cells equipped with the BiP reporter system. Targeted integrants showed a strong correlation between productivity and MFI, reflecting the potential of this monitoring system as a screening readout for high producers. Taken together, these data demonstrate the utility of the endogenous BiP reporter system for the detection of real-time dynamic changes in endogenous UPR and its potential for applications in recombinant protein production during CHO cell line development.
Keywords: Cell lines; Chinese hamster ovary; Chinese Hamster ovary cells; Endoplasmic reticulum stress; Expression levels; Monitoring system; Recombinant protein productions; Reporter systems; Unfolded protein response; Animals; Antibody Formation; CHO Cells; Cricetinae; Cricetulus; Endoplasmic Reticulum Chaperone BiP; Endoplasmic Reticulum Stress; Recombinant Proteins; BiP; Cell engineering; Chinese hamster ovary (CHO); ER stress; Recombinant protein production; Unfolded protein response